2007
DOI: 10.1007/s00784-007-0136-x
|View full text |Cite
|
Sign up to set email alerts
|

The oral hygiene and denture status among residential home residents

Abstract: The aim of this study was to investigate the oral hygiene practices and denture status of elderly people living in a residential home. One hundred one elderly people living in Gurcesme Zubeyde Hanim Residential Home, Izmir-52 women (mean age 75.5 +/- 7.8) and 49 men (mean age 75.3 +/- 8.8)-participated in an interview. Their oral hygiene practices, self-perceived oral health, denture status, and needs of denture were noted down. Self-perceived oral health was very bad in 9.9%, bad in 47.5%, good in 33.7%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
20
3
1
Order By: Relevance
“…A wide-range discussion is difficult, as there are very few studies on the subject-matter in the available literature. Results different from ours, concerning the correlation between education level and the use of removable dentures, were obtained by Akar and Ergul [5] who did not find such Pol J Public Health 2014;124 (2) a correlation for the elderly residents in nursing homes in Turkey. Evren et al [6] discovered that edentulous patients with a low education and income levels did not wear any dental replacements significantly more often.…”
Section: Discussioncontrasting
confidence: 70%
“…A wide-range discussion is difficult, as there are very few studies on the subject-matter in the available literature. Results different from ours, concerning the correlation between education level and the use of removable dentures, were obtained by Akar and Ergul [5] who did not find such Pol J Public Health 2014;124 (2) a correlation for the elderly residents in nursing homes in Turkey. Evren et al [6] discovered that edentulous patients with a low education and income levels did not wear any dental replacements significantly more often.…”
Section: Discussioncontrasting
confidence: 70%
“…However, brushing alone, in some conditions, can be an ineffective method of denture disinfection 3,6 . As many elderly individuals have difficulty in maintaining oral and denture hygiene as a consequence of diminished manual dexterity, impaired vision or associated debilitating conditions 15 , it is recommended that mechanical and chemical denture cleaning should be combined 5,8,12,[16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the decreased prevalence of edentulism, decreased incidence of tooth loss in Europe and other developed countries, and an increasing interest in oral implants, the vast majority of people with complete or partial edentulism continue to receive conventional prosthodontic treatment . Studies were carried out in several countries and reported the most frequent weakness is inadequate retention of mandibular complete dentures . Although in many cases the prosthesis used by this population group presents acceptable occlusion and integrity, the elderly seldom visit the dentist even though their dentures are often old and may require repair .…”
mentioning
confidence: 99%